Trade cards in the British Museum Banks Collection - Banks, Sarah Sophia, 1744-1818; Banks, Joseph, Sir, 1743-1820
Advertisements and trade cards from ca. 1790 to the mid-19th century collected by Sir Joseph Banks. Reels 1-17, Agricultural implement makers to Woolen drapers; reel 18, Various; reel 19, Foreign.